CeO2-Blended Cellulose Triacetate Mixed-Matrix Membranes for Selective CO2 Separation - Regmi, Chhabilal; Ashtiani, Saeed; Sofer, Zdeněk; Hrdlička, Zdeněk; Průša, Filip; Vopička, Ondřej; Friess, Karel (Membranes, 2021)
Due to the high affinity of ceria (CeO2) towards carbon dioxide (CO2) and the high thermal and mechanical properties of cellulose triacetate (CTA) polymer, mixed-matrix CTA-CeO2 membranes were fabricated. A facile solution-casting method was used for the fabrication process. CeO2 nanoparticles at concentrations of 0.32, 0.64 and 0.9 wt.% were incorporated into the CTA matrix. The physico-chemical properties of the membranes were evaluated by SEM-EDS, XRD, FTIR, TGA, DSC and strain-stress analysis. Gas sorption and permeation affinity were evaluated using different single gases. The CTA-CeO2 (0.64) membrane matrix showed a high affinity towards CO2 sorption. Almost complete saturation of CeO2 nanoparticles with CO2 was observed, even at low pressure. Embedding CeO2 nanoparticles led to increased gas permeability compared to pristine CTA. The highest gas permeabilities were achieved with 0.64 wt.%, with a threefold increase in CO2 permeability as compared to pristine CTA membranes. Unwanted aggregation of the filler nanoparticles was observed at a 0.9 wt.% concentration of CeO2 and was reflected in decreased gas permeability compared to lower filler loadings with homogenous filler distributions. The determined gas selectivity was in the order CO2/CH4 > CO2/N2 > O2/N2 > H2/CO2 and suggests the potential of CTA-CeO2 membranes for CO2 separation in flue/biogas applications.
Keywords: inorganic fillers; greenhouse gas; composite membrane; gas separation